Total Quality Management (TQM) in an Effort to Improve Education Services Through Teachers and Education Personnel at State Vocational High School 1 Dlanggu Mojokerto - Setyawan, Antonius Yudha; Nasir, M. Jamal Abdul; Wijayanti, Tri Cicik (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This research was conducted with the aim of analyzing and knowing how to implement, monitor, and evaluate TQM in improving education services through teachers and education staff in schools and how efforts are made to maintain good education services in an educational institution. This research uses a qualitative approach to the type of research using case studies. With research subjects, namely the principal and all managerial parties of Sekolah Menegah Kejuruan Negeri 1 Dlanggu, Data collection techniques include interviews, observation, and documentation. The results of the research that has been done, it shows that the implementation of TQM at Sekolah Menengah Kejuruan Negeri 1 Dlanggu in improving education services involves focusing educational services on customer needs, involving all school parties in realizing school goals, and always making continuous improvements. Likewise, monitoring continues to be carried out by school principals and representatives of quality management to find out customer needs. Evaluation is carried out by assessing the needs that have been met by the school by focusing on key performance indicators and the vision, mission, and goals of the school. Various efforts have been made to maintain the quality of education services, namely by fulfilling the needs of internal and external stakeholders, increasing the competitiveness and quality of graduates, and building a good culture—a culture that is in accordance with the work culture of each skill competency or major at Sekolah Menengah Kejuruan Negeri 1 Dlanggu.